Barriers to Menstrual Hygiene Management (MHM) Behavior for Adolescents with Disabilities: Systematic Literature Review - Elfiyani, Nur Khotimah; Arinda, Yosi Duwita; Pratomo, Hadi (The Center for Disability Studies and Services Brawijaya University, 2025)
The issue of reproductive health among adolescents with disabilities is frequently disregarded, primarily due to the prevailing misconception that they lack sexual desire. This situation gives rise to inadequate reproductive healthcare and education for this vulnerable group. The issue of menstrual health, particularly among adolescents with disabilities, has been the subject of only limited research and attention. The present study set out to examine the obstacles encountered by adolescents with disabilities in dealing with menstruation and to shed light on the prevailing societal misunderstanding that they are not asexual beings. The study thus sought to underscore the necessity for further attention to be given to reproductive health education for people with disabilities. A systematic literature review was conducted using the PRISMA method. A comprehensive database search was conducted on ScienceDirect, SpringerLink, ProQuest, and PubMed to identify studies that met the specified criteria. The search was limited to articles published between 2018 and 2022. The ten articles that met the inclusion criteria for the final review revealed that the obstacles encountered included a paucity of understanding about the severity of menstrual symptoms experienced by adolescents with disabilities, a paucity of information and support from families, and a paucity of knowledge regarding MHM in adolescents with disabilities. There is a need for training on personal hygiene for families and caregivers to better assist adolescents with disabilities in managing menstruation, along with targeted reproductive health education, to improve their overall quality of life.